Σ-Hole triel bonds in aluminium derivatives. Issue 3 (3rd January 2023) - Tabernero, Vanessa; Teresa Muñoz, M.; Palenzuela, Miguel; Gomila, Rosa M.; Frontera, Antonio; Mosquera, Marta E. G.
Abstract : The synthesis, X-ray characterization and DFT study of a new mononuclear aluminium compound exhibiting an intramolecular σ-hole triel bonding interaction is described. Abstract : This communication reports the synthesis and X-ray characterization of a new mononuclear aluminium compound exhibiting an intramolecular σ-hole triel bonding interaction. It is compared with a dinuclear aluminium compound, previously reported by us, where the aluminium atoms participate in two concurrent σ-hole triel bonding interactions. To our knowledge, such behaviour has not been previously described in the literature.